COVID-19 repellent cloth - Pandit, Sapan Kumar; Chauhan, Poonam; Sinhamahapatra, Apurba; Parekh, Yash; Ghalib Enayathullah, M.; Bokara, Kiran Kumar; Kumar, Aditya (Frontiers in Chemical Engineering, 2022)
In this research work, for the first time, we have developed and demonstrated a COVID-19 repellent coating on cotton cloth that not only repels the virus but also most of the human body fluids (superhemophobic). The coating was tested in the BSL3 lab. The controlled experiments revealed no significant increase in the log viral particles on coated fabric compared to the uncoated surface, evidence that the coated fabric resisted the SARS-CoV-2 inoculum. Further, the coated cloth exhibited excellent dust-free nature and stain resistance against body fluids (blood, urine, bovine serum, water, and saliva aerosol). It also shows sufficient robustness for repetitive usage. The fabrication process for the developed COVID-19 repellent cloth is simple and affordable and can be easily scaled up for mass production. Such coating could be applied on various surfaces, including daily clothes, masks, medical clothes, curtains, etc. The present finding could be a mammoth step towards controlling infection spread, including COVID-19.